IQGAP scaffold proteins are the multifunctional regulators of cellular signaling and malignant transformation - P. A. Skovorodnikova; M. S. Chesnokov; A. A. Budko; I. F. Kustova; N. L. Lazarevich (Успехи молекулярной онкологии, 2017)
Scaffold proteins coordinate the assembling of multicomponent protein complexes and participate in transduction of cellular signals via multiple signaling pathways therefore acting as important regulators of cell properties. IQ Motif Containing GTPase Activating Proteins (IQGAPs) are promising targets for studying the role of scaffold proteins in intracellular signaling regulation and development of cancer and other diseases. IQGAP family includes 3 proteins (IQGAP1, IQGAP2 and IQGAP3) that differ considerably by their expression patterns and functions. Distinct genomic aberrations and expression changes in various tumors were reported for all three IQGAP family members. The present paper thoroughly reviews the structure of IQGAP proteins, their involvement in regulation of cell characteristics and interactions with components of intracellular signaling pathways. Special attention is given to the up-to-date data on deregulation of IQGAP genes functions in different tumor types, analysis of their possible role in tumor progression and their associations with clinicopathological tumor characteristics.